Multidisciplinary group therapy for refugee patients with PTSD/CPTSD and psychosomatic comorbidity - Marian Cabrejas; Giuseppe Daverio (Forum for Group Psychotherapies and Processes)
In this paper, we present a pilot project for multidisciplinary, time-limited, therapeutic treatment for patients living in exile, severely traumatized by war and/ or torture, suffering from complex post-traumatic stress disorder (PTSD), and psychosomatic comorbidity. The project was developed and conducted at a specialized, public out-patients unit in Gothenburg, Sweden, during February 2022 and June 2023. The authors, a psychologist and a physiotherapist, questioned the dualistic perspective in trauma treatment and aimed to test a new therapeutic model for group setting integrating two clinical approaches, i.e., psychodynamic process-oriented group treatment, and Norwegian psychomotor physiotherapy. The model is characterized by a trauma-informed and culturally sensitive perspective. The background and development of the project is described, along with clinical experience and reflections on the potentialities, and challenges of a co-therapeutic group setting integrating two professions in the treatment of severe psychic trauma.